Sequential injection-differential pulse voltammetric immunosensor for hepatitis B surface antigen using the modified screen-printed carbon electrode - Jantima Upan (2020)
© 2020 Elsevier Ltd A label-free electrochemical immunosensor was developed for the determination of hepatitis B surface antigen (HBsAg), a biomarker of hepatitis B virus (HBV). It is based on the speciﬁc binding of antigen-antibody on the electrode surface, which hindered the oxidation of silver nanoparticles (AgNPs) used as redox probe and hence reduced its oxidation current. The screen-printed carbon electrode (SPCE) was modified with carbon nanotube decorated with gold nanoparticles (AuNPs-CNT) and silver nanoparticles. The AuNPs provide good biocompatibility and large surface area for densely immobilizing the hepatitis B surface antibody (HBsAb) on the electrode, which helps to improve the signal. AgNPs act as a sensing probe in differential pulse voltammetric (DPV) detection. In addition, a sequential injection (SI) system was employed as an automated solution handling and minimizing chemical consumption. Characterization of the developed immunosensor by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) confirmed the successful modification/immobilization in various steps of immunosensor fabrication. The percentage of the decrease in oxidative peak current of AgNPs was directly proportional to the HBsAg concentration. The linear range of 1–40 ng mL−1 with a detection limit of 0.86 ng mL−1 HBsAg were achieved. The proposed method is economical, efficient, and useful for clinical analysis.